The Oxytocin Receptor Gene (OXTR) Variant rs53576 Is Not Related to Emotional Traits or States in Young Adults - Conner, Tamlin S.; McFarlane, Karma G.; Choukri, Maria; Riordan, Benjamin C.; Flett, Jayde A. M.; Phipps-Green, Amanda J.; Topless, Ruth K.; Merriman, Marilyn E.; Merriman, Tony R. (Frontiers in Psychology, 2018)
BACKGROUND: To understand the genetic underpinnings of emotion, researchers have studied genetic variants in the oxytocin system, a hormone and neurotransmitter important to socio-emotional functioning. The oxytocin receptor gene (OXTR) variant rs53576 has been associated with emotional traits such as positive affect and related constructs such as optimism and self-esteem. Individuals carrying the A allele (AG and AA genotypes) of rs53576 have been found to score lower in these traits when compared to GG homozygotes, although not always. Given recent mixed evidence regarding this polymorphism, replication of these associations is critical. METHODS: Using a cross-sectional design, the present study tested the association between rs53576 and a wide variety of emotional traits and states in a sample of 611 young adults ages 18 - 25 of various ethnicities (European, Asian, Māori/Pacific Islander, other). Participants completed standard trait measures of positive and negative affect, depressive symptoms, life engagement, psychological well-being, optimism, and self-esteem. They also completed state measures of positive and negative affect and life engagement for 13-days using Internet daily diaries. RESULTS: Controlling for ethnicity and gender, variation at the OXTR variant rs53576 obtained from blood samples was not related to any of the emotional traits or states. This null finding occurred despite measuring emotions in ‘near to real time’ using daily diaries and having sufficient power to detect a medium effect size difference between homozygous genotype groups. CONCLUSION: These findings suggest that variation at the rs53576 locus may not be as involved in emotional differences as initial studies suggested.